Situational diagnostic of the breeding of guinea pigs in Cajamarca - Aguilar R., Gisel (2011)
A survey was conducted in July 2004 to 160 families rearing Guinea pigs in the district of Santa Cruz, Cajamarca, with the aim of characterizing the production system of these animals. Men were more than 50 years of age (44.6%) and wives were mainly between 31 to 50 years old (42%). Primary school was the main grade of instruction. The main labour activity of the head of the family was agriculture (95.4%) and housekeeping for women (97.2%). Raising guinea pigs was mainly driven by the housewife under a family or traditional system. There were 20.4 guinea pigs on average per family, reared regardless of class, sex and age, preferably in the kitchen (88.8%), free (73.8%) or in pools (21.9%). Feeding was based on forages, weeds and kitchen waste. The main diseases reported were ectoparasites (90.1%) and the «plague» (76%). Guinea pigs were used for consumption and sale (71.2%) or only for home consumption (28.2%). Most of producers (96.2%) indicated that they do not have services such as technical assistance, credit, inputs, etc, and 67.5% considered that they would improve their productivity if technical assistance was available.